Viskosimeter Digital Menggunakan Water Flow Sensor G1/2 Berbasis Mikrokontroller 8535 - kalam tambah tua siregar (Saintia Fisika, 2013)
Designing digital viscosimeter using water flow sensor application G1/2 ATMega853 AVR microcontroller based useful for measuring the viscosity of the fluid in a practical value. The core of this tool is used the sensor water flow sensor G1/2 which is a type of flow sensor, which when energized by the fluid can be determined rotations per second (rps). Sensor works on a certain viscosity which the more viscous fluid will flow the smaller the value generated rps. Measurement capability of this tool is in the range of 8-22 rps or on the viscosity range from 0.8340 - 42.3878 cP. Data of sensor processing used a microcontroller ATMega 8535 chip and language used is a C language program while the data processing system using Lagrange interpolation. Keywords: fluid, rotation, viscosity